Electronic Traffic Law Enforcement to Reduce Traffic Violations in Indonesia - Sitoresmi, Sitoresmi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. UULLAJ as a form of legal certainty in terms of protecting human rights, especially in driving on the road, must be strengthened by good and integrated law enforcement officers. The Indonesian National Police are traffic law enforcement officers who have an important role in providing services to the community in the traffic sector, such as order, smoothness, and improving the quality of the community in driving, because the main factor supporting modern human productivity is traffic. The legal basis for taking action against violations on the road using electronic devices or ETLE is regulated in Article 272 of Law Number 22 of 2009 which states that to support the activities of taking action against traffic and road transportation violations, electronic equipment can be used, and the results can be used as evidence in court. Based on Article 23Government Regulation (PP) Number 80 of 2012Regarding the Procedures for Inspecting Motor Vehicles on the Road and Enforcement of Traffic and Road Transportation, enforcement of traffic and road transportation violations is also regulated based on findings in the inspection process of motor vehicles on the road, reports, and/or electronic equipment recordings. Based on data from the Dirgakkum Korlantas Polri from national accident data in 2023, there were almost 152 thousand accidents, almost 18,357 fatalities, 11,689 serious injuries, and 134,800 minor injuries throughout Indonesia. The implementation of ETLE in the East Java Regional Police area has only been installed in several areas or police stations with several points, namely the East Java Regional Police Traffic Directorate (21 points), Surabaya Police (24 points), Madiun Loc. city Police (4 points), Gresik Police (5 points), Lamongan Police (2 points), Tulungagung Police (2 points), Batu Police (1 point), Sidoarjo Police (3 points).